A Trajectory Planning Method for Optimal Energy Consumption of the Hydraulic Excavator - Zhang Yunyue; Sun Zhiyi; Sun Qianlai; Wang Yin; Yang Jiangtao (Jixie chuandong)
In order to reduce the movement energy consumption of the hydraulic excavator and realize the reasonable and effective operation of each joint, a joint interpolation method based on a T-type velocity curve is proposed to realize the optimal energy consumption trajectory planning of the hydraulic excavator. In this method, the speed of each joint is set as uniform acceleration, constant velocity, and uniform deceleration to ensure the stability of the hydraulic excavator in the operation process. Under the constraint conditions of the joint angle, angular velocity, and angular acceleration, the improved adaptive genetic algorithm is used to optimize the uniform acceleration (deceleration) and constant velocity motion time of each joint, obtain the optimal motion curve of each joint, and realize the optimal energy consumption trajectory planning of the hydraulic excavator. The interpolation programming method based on the T-type velocity curve is simulated and compared with the interpolation results of the quartic polynomial under the same conditions. The experimental results show that the trajectory planned by this method has low energy consumption, avoids unnecessary movement of each joint, effectively reduces friction loss, and makes the excavator complete the operation smoothly and with low energy consumption.